A pediatric case of NF1 and moyamoya syndrome: Neuropsychological evaluation pre- and post-EDAS. Issue 3 (3rd July 2021) - DeDios-Stern, Samantha; Ventura, Lea M.
Abstract: Studies have shown that a subset of patients with neurofibromatosis type 1 (NF1) experience associated vascular conditions, with moyamoya syndrome one of the most common comorbidities. While NF1 and moyamoya syndrome are each associated with neurocognitive deficits, no neuropsychological data has been presented for an individual with comorbid NF1 and moyamoya syndrome, particularly pre- and post-re-vascularization surgery. The present case describes the neuropsychological profile of a bilingual Latina girl with NF1 and moyamoya syndrome, who was assessed pre- (age 5 years, 9 months) and post-EDAS (age 6 years, 1 month). Each evaluation included a clinical interview and comprehensive battery of neuropsychological tests. Results of pre-EDAS evaluation documented significant deficits in sustained attention, daily executive functioning, and academic abilities, and she met criteria for ADHD-combined type. Results of post-EDAS evaluation revealed generally stable abilities with relative improvements in social, emotional, and behavioral functioning, but relative decline in visuospatial skills, visual spatial learning/memory, and aspects of executive functioning. Math abilities also remained consistently poor and she was diagnosed with a specific learning disability (mathematics). This case study adds to the current literature by being among the first to present pre- and post-surgical neuropsychological data for a child with NF1 and moyamoya syndrome. Findings are discussed in the context of previous literature, the importance of individual socio-cultural considerations in the case (i.e., language, education, culture), and recommendations for future research.